2018
DOI: 10.1103/physrevd.98.084041
|View full text |Cite
|
Sign up to set email alerts
|

Towards nonsingular rotating compact object in ghost-free infinite derivative gravity

Abstract: The vacuum solution of Einstein's theory of general relativity provides a rotating metric with a ring singularity, which is covered by the inner and outer horizons, and an ergo region. In this paper, we will discuss how ghost-free, quadratic curvature, Infinite Derivative Gravity (IDG) may resolve the ring singularity. In IDG the non-locality of the gravitational interaction can smear out the delta-Dirac source distribution by making the metric potential finite everywhere including at r = 0. We show that the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 82 publications
4
69
0
Order By: Relevance
“…However, it is reasonable to assume that, once that quantum gravity effect are taken into account, singularities will be regularized. The structure and properties of the corresponding non-singular black holes is largely unknown, in part due to our lack of knowledge about the dynamics in quantum gravity, although there have been many and diverse attempts at constructing geometries or toy models that aim at capturing the leading effects beyond general relativity [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reasonable to assume that, once that quantum gravity effect are taken into account, singularities will be regularized. The structure and properties of the corresponding non-singular black holes is largely unknown, in part due to our lack of knowledge about the dynamics in quantum gravity, although there have been many and diverse attempts at constructing geometries or toy models that aim at capturing the leading effects beyond general relativity [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] where it was shown that higher derivative gauge theories can be made ghost-free. In the gravitational context the same class of nonlocal actions were useful to obtain ghost-free nonsingular cosmological [14][15][16][17][18] and blackhole [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] solutions. Such nonlocal models were also applied in the framework of inflationary cosmology [34], and thermal field theory [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It is a direct manifestation of the non-trivial nature of quantum vacuum [20], which occurs whenever a quantum field is bounded in a finite region of space; such a confinement gives rise to a net attractive force between the confining plates, whose intensity has been successfully measured [21]. Since the foundational paper [22], the Casimir effect has been largely investigated in both flat [23] and curved [24] background, and in particular in quadratic theories of gravity [25], which have been studied also in other frameworks [26]. Further interesting applications have been addressed in the context of Lorentz symmetry breaking [27] and flavor mixing of fields [28].…”
Section: Introductionmentioning
confidence: 99%